2013
DOI: 10.1177/0146167213478200
|View full text |Cite
|
Sign up to set email alerts
|

Collective Futures: How Projections About the Future of Society Are Related to Actions and Attitudes Supporting Social Change

Abstract: We identified the active ingredients in people's visions of society's future ("collective futures") that could drive political behavior in the present. In eight studies (N = 595), people imagined society in 2050 where climate change was mitigated (Study 1), abortion laws relaxed (Study 2), marijuana legalized (Study 3), or the power of different religious groups had increased (Studies 4-8). Participants rated how this future society would differ from today in terms of societal-level dysfunction and development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 58 publications
5
77
0
2
Order By: Relevance
“…There is anecdotal evidence that self-consumption projects can facilitate access to affordable heat or electricity where the cost of alternative fuels is relatively high [164,165], typically in off-gas and/or off-electricity-grid remote locations [35,140,166] or locations that have ample low-cost woodfuel supply [167,168]. Such conditions can make community micro-grids and facility projects the most financially attractive option available [36,50,140,166].…”
Section: Overviewmentioning
confidence: 99%
“…There is anecdotal evidence that self-consumption projects can facilitate access to affordable heat or electricity where the cost of alternative fuels is relatively high [164,165], typically in off-gas and/or off-electricity-grid remote locations [35,140,166] or locations that have ample low-cost woodfuel supply [167,168]. Such conditions can make community micro-grids and facility projects the most financially attractive option available [36,50,140,166].…”
Section: Overviewmentioning
confidence: 99%
“…These people are especially concerned with addressing this decline, supporting actions and policies intended to restore community bonds (unless they believe society is incapable of changing; Kashima et al, 2009). Accordingly, the desire to create a more moral and caring society motivates action across diverse social and political issues (Bain, Hornsey, Bongiorno, Kashima, & Crimston, 2013).…”
Section: Addressing Climate Change To Create a More Moral And Carinmentioning
confidence: 99%
“…The second and third domains focused on two fundamental dimensions people use to evaluate their society and other groups: competence (our capabilities and skills) and communality (how caring and warm we are to each other; e.g., Cuddy et al 2008;Fiske et al 2007). Bain et al (2012Bain et al ( , 2013Bain et al ( , 2015 showed that the communality domain is strongly and consistently linked to people's willingness to act on climate change. The fourth domain was development; relating climate change to the economy and technology (e.g., UNEP, 2011;Fabian, 2015;Nisbet, 2009), which is also an effective motivator of climate change behavior (Bain et al 2012(Bain et al , 2015.…”
Section: Framing Climate Change In Interpersonal Communicationmentioning
confidence: 99%